The Impact of Case Management on Elderly Patients with Chronic Obstructive Pulmonary Disease - Li N; Wang W; Lv Y; Li C; Mu X (International Journal of COPD)
Na Li,1 Wenjing Wang,2 Yinyin Lv,1 Caihong Li,1 Xiangdong Mu3 1Department of Nursing, Beijing Tsinghua Changgung Hospital, School of Clinical Medicine, Tsinghua Medicine, Tsinghua University, Beijing, People’s Republic of China; 2School of Nursing, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 3Department of Pulmonary and Critical Care Medicine, Beijing Tsinghua Changgung Hospital, School of Clinical Medicine, Tsinghua Medicine, Tsinghua University, Beijing, People’s Republic of ChinaCorrespondence: Xiangdong Mu, Department of Pulmonary and Critical Care Medicine, Beijing Tsinghua Changgung Hospital, School of Clinical Medicine, Tsinghua Medicine, Tsinghua University, Beijing, People’s Republic of China, Tel +86 15810981402, Email mxda02600@btch.edu.cnPurpose: This study aims to investigate the effects of case management on elderly patients with chronic obstructive pulmonary disease (COPD) and compare changes in pulmonary function indicators, quality of life, dyspnea, and inhaled medication adherence before and after case management.Patients and Methods: A total of 199 elderly COPD patients were enrolled from Beijing Tsinghua Changgung Hospital between January 2020 and November 2023. We implemented case management programs including regular patient education, personalized interventions, continuous support systems, and timely feedback mechanisms, and subsequently collected patient data at 1, 3, 6, and 12 months after initiating case management.Results: After one year of case management, pulmonary function indicators (FEV1/FVC, FEV1, FEV1%pred, MMEF75/25 and MMEF75/25%) in elderly patients with COPD showed significant improvement (P < 0.001). The CAT score decreased from 17.96± 6.57 (mean ± standard deviation) to 11.80± 6.50, and mMRC score decreased from 2.35± 0.66 to 1.14± 0.92 (p< 0.001). Additionally, 77.9% (155/199) of patients were able to maintain their use of the inhaler for 1 year.Conclusion: This study confirmed the significant role of case management in improving respiratory function, quality of life, and dyspnea in elderly patients with COPD. These findings not only provide a valuable reference for clinicians and patients, but also provide a strong foundation for further optimization of management strategies for elderly patients with COPD.Keywords: chronic obstructive pulmonary disease, case management, elderly patients, respiratory function, adherence for inhaled therapies